Factors Influencing the Acceptance of Covid-19 Vaccines in a Country with a High Vaccination Rate - Zorondo-Rodriguez, F (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Control of the COVID-19 pandemic largely depends on the effectiveness of the vaccination process. An understanding of the factors that underlie the willingness to accept vaccination contributes pivotal information to controlling the pandemic. We analyzed the association between the willingness to accept the available COVID-19 vaccines and vaccine determinants amidst the Chilean vaccination process. Individual-level survey data was collected from 744 nationally representative respondents and multivariate regression models were used to estimate the association between outcome and explanatory variables. We found that trust in COVID-19 vaccines, scientists, and medical professionals significantly increased the willingness to: accept the vaccines and booster doses, as well as annual vaccinations and the vaccination of children. Our results are critical to understanding the acceptance of COVID-19 vaccines in the context of a country with one of the world’s highest vaccination rates. We provide useful information for decision-making and policy design, in addition to establishing guidelines regarding how to effectively explain vaccination programs to citizens. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.